Molecular Analysis and Modeling of Hepatitis E Virus Helicase and Identification of Novel Inhibitors by Virtual Screening. (30th August 2018) - Parvez, Mohammad K.; Subbarao, Naidu
Abstract : The hepatitis E virus- (HEV-) helicase as a novel drug-target was evaluated. While cell culture model was used for mutational characterization of helicase, in silico protein modeling and virtual screening were employed to identify helicase inhibitors. None of the saturation mutant replicons significantly affected RNA replication. Notably, mutants encompassing the Walker motifs replicated as wild-type, showing indispensability of nucleotides conservation in viability compared to known criticality of amino acids. A 3D modeling of HEV-helicase and screening of a compound dataset identified ten most promising inhibitors with drug likeness, notably, JFD02650, RDR03130, and HTS11136 that interacted with Walker A residues Gly975, Gly978, Ser979, and Gly980. Our model building and virtual identification of novel helicase inhibitors warrant further studies towards developing anti-HEV drugs.